Attention Deficit Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The go-no-go paradigm was used in the evaluation of children with attention deficit disorder (ADD) at the Dept of Pediatrics, Division of Neurology and Evaluation Center for Learning, Northwestern Univ Medical School, Evanston Hospital, Evanston, IL.